The possibility of using waqf to finance the Malaysian federal government's public expenditure - Azrai Azaimi Ambrose, Azniza Hartini; Mohamed Haneef, Mohamed Aslam; Hanafi, Hanira (Department of South East Asian Studies, University Malaya, 2018)
The purpose of this paper is to examine thepossibility of using waqf to finance the federal government’s public expenditures in Malaysia. The arguments werebasedon the primary data gathered from semi-structuredinterviews with waqf experts. The resultshows that waqf can financethe Malaysian federal government’s public expenditure for three reasons; Shari’ah permissibility, there is evidence of implementation in past Muslim economiesand political will from the federal government. This study is motivatedby Malaysia’s persistent primary deficit, Malaysia’s rising debt to GDP, and the versatile nature of waqf that could address these problems. Due to the exploratory nature of this study, qualitativeresearch was conductedthrough the employment of semi-structuredinterviews. The thematic analysis was then performedon the interview transcripts. Literary evidencewasalso mentioned to ensure the concurrentvalidity of the mentioned results. The findings of this paper may add to the existing literature on the solutions to the burgeoning government expenditure and debt. Even more so, this article motivates researchers to explore the arising issues stemming from this particular waqf implementation.